2018
DOI: 10.1200/jco.2018.36.4_suppl.764
|View full text |Cite
|
Sign up to set email alerts
|

M7824 (MSB0011359C), a bifunctional fusion protein targeting PD-L1 and TGF-β, in patients with heavily pretreated CRC: Preliminary results from a phase I trial.

Abstract: 764 Background: Inhibiting the transforming growth factor β (TGF-β) pathway, which plays a key role in tumor immunosuppression, may enhance the response to programmed death 1/programmed death ligand 1 (PD-1/PD-L1) monoclonal antibodies (mAbs). M7824 (MSB0011359C) is an innovative first-in-class bifunctional fusion protein composed of a mAb against PD-L1 fused with the extracellular domain of TGF-β receptor II, which serves as a TGF-β “trap.” We report results in patients (pts) with heavily pretreated colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Overall, the pharmacokinetic profile of bintrafusp alfa in Asian patients (Table 2) was similar to that in the global study [8,9]. Based on an integrated analysis of clinical activity and safety, the pharmacokinetic profile of bintrafusp alfa observed in the dose-escalation phase of both studies, the pharmacodynamic profile of bintrafusp alfa from the global study, and reported data from cohorts of these studies exploring 500-mg and 1200-mg Q2W dosing [12][13][14]19], a dose level of 1,200 mg was evaluated in multiple additional expansion cohorts [8,20].…”
Section: Study Completedmentioning
confidence: 88%
See 1 more Smart Citation
“…Overall, the pharmacokinetic profile of bintrafusp alfa in Asian patients (Table 2) was similar to that in the global study [8,9]. Based on an integrated analysis of clinical activity and safety, the pharmacokinetic profile of bintrafusp alfa observed in the dose-escalation phase of both studies, the pharmacodynamic profile of bintrafusp alfa from the global study, and reported data from cohorts of these studies exploring 500-mg and 1200-mg Q2W dosing [12][13][14]19], a dose level of 1,200 mg was evaluated in multiple additional expansion cohorts [8,20].…”
Section: Study Completedmentioning
confidence: 88%
“…Additionally, a manageable safety profile and encouraging early signs of clinical activity have been reported with bintrafusp alfa across all doses tested (0.3-20 mg/kg) in a first-in-human global phase I, 3 + 3 dose-escalation study (NCT02517398), which enrolled patients with heavily pretreated advanced solid tumors [8]. This promising antitumor activity and manageable tolerability profile have also been demonstrated in multiple expansion cohorts of the same trial [11][12][13][14].…”
Section: Study Completedmentioning
confidence: 98%
“…Although studies investigating the small-molecule type I TGFβ serine/threonine kinase inhibitors in combination with anti–PD-1 antibodies are still ongoing, early clinical data has been reported for M7824, a bifunctional fusion protein comprised of anti–PD-L1 and the extracellular domain of the type II TGFβ receptor that effectively functions as a TGFβ trap (52). Although clinical responses are being reported in pre-treated patients with a variety of solid tumor types, larger studies with longer follow-up will be necessary to fully assess the clinical utility and ideal patient population of this therapeutic approach (5457). This work underscores the importance of gaining a mechanistic understanding of the impact of pharmacologic agents on the tumor immune microenvironment and how these alterations may, in turn, affect the ultimate generation of effector antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…289 M7824 showed a manageable safety profile and encouraging clinical efficacy in phase 1 clinical trials, including patients with advanced solid tumors, NSCLCs, recurrent glioblastoma, cervical cancer, metastatic TNBC, heavily pretreated CRC, or human papillomavirus (HPV)-associated cancers. [290][291][292][293][294][295][296] M7824 is now being evaluated in a phase 2 clinical trial for patients with advanced/metastatic biliary tract cancer, gallbladder cancer, recurrent respiratory papillomatosis, thymoma, CRC, head and neck squamous cell cancer, advanced pancreas cancer, or recurrent prostate cancer. 297 Moreover, the evaluation of M7824 for patients with advanced NSCLC or biliary tract cancer is now under investigation in phase 3 clinical trials.…”
Section: Targeting Tgfβ In Cancer Therapy: Challenges and Opportunitiesmentioning
confidence: 99%